1991
DOI: 10.1029/91rs01873
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of ionospheric imaging by tomography

Abstract: The potential of imaging large ionospheric structures by applying tomographic techniques has only been proposed recently and has already received interest and increasing attention by workers in ionospheric research. In the combined case of an idealized plane geometry and complete and continuous data extending to +_oo the inversion is exact and unique. This is no longer the case if any of the idealized conditions are removed. Specifically, we investigate the limitations arising from limited angles, sampled data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 14 publications
0
53
0
Order By: Relevance
“…Radio tomography has also been used to image the latitudinal structure of the trough. The method in this case suffers from limited ray-path geometry set by the configuration of the satellites and receivers (Yeh and Raymund, 1991) and requires a priori information to support the reconstruction process (Raymund et al, 1993). In another inversion application Mitchell and Spencer (2003) presented an algorithm using GPS observations that yielded the timeevolving, three-dimensional ionospheric electron concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Radio tomography has also been used to image the latitudinal structure of the trough. The method in this case suffers from limited ray-path geometry set by the configuration of the satellites and receivers (Yeh and Raymund, 1991) and requires a priori information to support the reconstruction process (Raymund et al, 1993). In another inversion application Mitchell and Spencer (2003) presented an algorithm using GPS observations that yielded the timeevolving, three-dimensional ionospheric electron concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The relative merits of different methods to obtain TEC for CIT have been discussed by Yeh and Raymund [1991], and the importance of geometry was stressed by several authors, including Brown and Ganguly [2001]. The typical observational geometry for group delay or differential phase TEC measurement is not favorable to the estimation of the vertical structure of the ionosphere, including the height of the F 2 peak.…”
Section: Introductionmentioning
confidence: 99%
“…There are substantial differences between medical and ionospheric scenarios mainly due to the geometry of the problem. CIT has, in fact, limitations such as limited angle observations and uneven/sparse distribution of the ground stations [4,5] that make the solution unstable and difficult to solve. However, the capability of the method was demonstrated by Mitchell et al [6] where, along a quasi-2D plane, features in the electron density were revealed at mid and auroral latitudes.…”
Section: Introductionmentioning
confidence: 99%